Current practice in mandibular third molar surgery. A national survey of British Association of Oral Surgeons membership. (4th March 2016) - Devine, M.; Gerrard, G.; Renton, T.
Abstract: Objective: The aim of this survey was to evaluate current practice in mandibular third molar (M3M) surgery within the British Association of Oral Surgeons (BAOS) membership against current evidence and relevant guidelines. Method: An online questionnaire survey was active from March to June 2015. Results: A total of 250 BAOS members (48%) responded to the survey. About 52% were registered Oral Surgery specialists. Exactly, 36% stated that M3M surgery comprised 50–75% and 17% stated that M3M surgery comprised over 75% of their workload. About 73% would recommend coronectomy for high‐risk M3Ms; however, 53% had difficulty in accessing cone beam CT (CBCT) scanning. Most practitioners undertook a two‐stage written consent informing patients of the possibility of numbness, altered sensation or pain as a result of inferior alveolar or lingual nerve injury; however, there were significant variations in how this was communicated. Most surgeons operated mainly under local anaesthesia, using a triangular buccal flap access; 27% routinely used lingual retraction. Buccal and distal bone removal followed by sectioning of the tooth was the most common approach, although 1% routinely used the lingual split technique. Over the last 5 years, each responder reported an average of 2 temporary and 0.4 permanent inferior alveolar nerve injuries (IANI), 1 temporary and 0.1 permanent lingual nerve injuries (LNI). Conclusion: This survey has highlighted the lack of access to CBCT scanning and the differences in approach to consent and surgical technique. The reported rates of nerve injury caused by M3M surgery were low; however, this may be due to a lack of post‐operative follow up.